Student difficulties in solving covariational problems - Sandie; Purwanto; Subanji; Erry Hidayanto (International Journal of Humanities and Innovation (IJHI), 2019)
This study discusses the difficulties of students in solving covariational problems. The study was conducted on 25 students with 6th-semester studies who had completed calculus courses. Students are asked to verbalize what they think while solving problems (think aloud). Next, students are interviewed with an in-depth interview technique to explore the thinking process. The results showed 88% of students had difficulties when given covariational problems. Students are familiar with mathematical problems with counting operations. When given a problem without information, students experience difficulties.